Discovery of circulating miRNAs as biomarkers of chronic Chagas heart disease via a small RNA-Seq approach - Villar, Silvina Raquel (2024)
Chagas disease affects approximately 7 million people worldwide in Latin America and is a neglected tropical disease. Twenty to thirty percent of chronically infected patients develop chronic Chagas cardiomyopathy decades after acute infection. Identifying biomarkers of Chagas disease progression is necessary to develop better therapeutic and preventive strategies. Circulating microRNAs are increasingly reliable biomarkers of disease and therapeutic targets. To identify new circulating microRNAs for Chagas disease, we performed exploratory small RNA sequencing from the plasma of patients and performed de novo miRNA prediction, identifying potential new microRNAs. The levels of the new microRNAs temporarily named miR-Contig-1519 and miR-Contig-3244 and microRNAs that are biomarkers for nonchagasic cardiomyopathies, such as miR-148a-3p and miR-224-5p, were validated by quantitative reverse transcription. We found a specific circulating microRNA signature defined by low miR-Contig-3244, miR-Contig-1519, and miR-148a-3 levels but high miR-224-5p levels for patients with chronic Chagas disease. Finally, we predicted in silico that these altered circulating microRNAs could affect the expression of target genes involved in different cellular pathways and biological processes, which we will explore in the future.